Pengaruh Kepemimpinan Dan Kompensasi Terhadap Loyalitas Agen Dan Dampaknya Terhadap Kinerja Agen Pada PT. BNI Life Insurance Di Kantor Pemasaran Agency II - gultom, elida (Jurnal Daya Saing, 2016)
Abstract: This study aims to determine the effect of leadership, compensation and agent loyalty against agent performance on PT. BNI Life Insurance at Marketing Agency II Office. The population in this study are all agents have the AAJI license certification with work tenure > 1 year on PT. BNI Life Insurance at Marketing Agency II Office consisting of 15 Cities in Indonesia with a total of as many agents as 785 people. The sampling in this study were taken by disproportionate stratified random sampling, using the formula of Taro Yamane in order to obtain as many as 89 people. The method used is quantitative method with data collection instruments that form questionnaire Likert scale models. Hypothesis testing is done via Path analysis techniques assisted with data processing devices Statistical Package of Social Science (SPSS) 17.0. Sub-structure analysis results 1 show that leadership and compensation significant effect on the loyalty of agents with contributions (donations) leadership to the loyalty of agents by 85.9% and 14.5% of compensation. While the Sub-Structure 2 shows that leadership, compensation and agent loyalty significant effect on the performance of agents. As for the contribution of leadership (X1) on the performance of the agent (Y) is expressed with a path coefficient of 27.3%. compensation (X2) by 20.4% and loyalty agent (X3) amounted to 52.3%. Keywords: Leadership, Compensation, Loyalty and Employee Performance